Male genital organs and accessory glands of the lesser mouse deer, Tragulus javanicus - Vidyadaran, M. K.; Sharma, R. S. K.; Sumita, S.; Zulkifli, I.; Razeem-Mazlan, A. (Allen Press Inc., 1999)
Gross anatomical features of the male genital organs and accessory genital glands of the lesser mouse deer (Tragulus javanicus) are described. The long fibroelastic penis lacks a prominent glans and is coiled at its free end to form two and one-half turns. Near the tight coils of the penis, on the right ventrolateral aspect, lies a U-shaped ventral process. The scrotum is prominent, unpigmented, and devoid of hair and is attached close to the body, high in the perineal region. The ovoid, obliquely oriented testes carry a large cauda and caput epididymis. Accessory genital glands consist of paired, lobulated, club-shaped vesicular glands, and a pair of ovoid bulbourethral glands. A well-defined prostate gland was not observed on the surface of the pelvic urethra. Many features of the male genital organs of T. javanicus are pleisomorphic, being retained from suiod ancestors of the Artiodactyla.